Pulmonary Adenocarcinoma Patient with Complex Mutations on EGFR Benefits from Furmonertinib after Acquiring Gefitinib Resistance: A Case Report - Wu, Guixian; Chen, Qian; Lv, Dongqing; Lin, Ling; Huang, Jing (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Background: Although epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have been proven a long-lasting treatment effect in pulmonary adenocarcinoma, most patients still progressed within one year due to the acquired resistance. Complex mutations of rare rare sites after acquiring resistance are rarely reported in pulmonary adenocarcinoma.Case Presentation: A 62-year-old woman was diagnosed with pulmonary adenocarcinoma with stage IV. Genetic testing at the initial treatment showed EGFR L858R positive. After being treated with gefitinib, persistent 2 years disease progression occurred due to drug resistance. The genetic testing showed that EGFR L858R was eliminated, while a rare rare complex mutation of L861Q/G719X appeared. After 160 mg furmonertinib was treated for 1 month, the primary tumor regressed and the intracranial lesions disappeared. The patient has achieved progression-free survival (PFS) for more than 20 months.Conclusion: Pulmonary adenocarcinoma with rare rare complex mutations in EGFR induced by gefitinib resistance and disease progression might benefit from furmonertinib treatment.
Keywords: drug resistance